ANALISIS KINERJA DAN BUDAYA MUTU DI IGD RS PKU MUHAMMADIYAH YOGYAKARTA II - Erwin Santosa; Yunita Pransisca (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2013)
Concern to quality service in nowadays becoming global issue that triggered by consciousness to give best service for patient or by request from eksternal side of hospital. Goverment push hospital to give good quality of service by giving evaluation of hospital standarization. PKU Muhammadiyah Hospital Jogjakarta unit II which new one of health service unit right now striving to improve quality of service. Result of the beginning observation findout evaluation of activity are often neglected, particularly on unit emergency. The objective of this observation is to find out performance and quality culture in management unit emergency of PKU Muhammadiyah Hospital Jogjakarta unit II, This observation using qualitative method with case study as observation plan that using interview as observation instrument involving board of management and officer of unit emergency of PKU Muhammadiyah Hospital Jogjakarta unit II. The Self Assesment accreditation in 2008 and first edition of accreditation standard in 2012 result show that quality service standard that using by unit emergency of PKU Muhammadiyah Jogjakarta unit II for develop their quality of service its guided line for survey of hospital accreditation in 2008 instructed by Indonesia health ministry that poured into activity guidance of unit emergency, but because lack availability of unit emergency officer make unit emergency can’t support implementation of unit emergency activity guidance. Working culture in unit emergency of PKU Muhammadiyah Hospital Jogjakarta unit II its only doing fast emergency response but not yet support quality service development because not yet develop service evaluation process. Service process evaluation hard to do because of limitation number of human resource. The result of unit emergency performance show by AKPPGD, DOA and result of accreditation in 2008 already achieve the standard, but not yet fulfill quality standard evaluation of health service management base on first edition of accreditation in 2012.